A novel biological model for training in percutaneous renal access. Issue 4 (2nd October 2019) - Vijayakumar, Mohankumar; Balaji, Sudharsan; Singh, Abhishek; Ganpule, Arvind; Sabnis, Ravindra; Desai, Mahesh
ABSTRACT: Objective : To develop a new model comprised of a bovine kidney within a chicken carcass for training in percutaneous renal access (PRA) and compare its effectiveness with the traditional mannequin model. Subjects, materials and methods : The study was conducted from January 2017 to June 2017. The content and the construct validity of the new model were confirmed after which it was compared with the traditional non-biological model for PRA. In all, 20 urology residents, with experience of <20 cases, were enrolled in the study. The parameters assessed were time to puncture, attempts to successful puncture, and fluoroscopy exposure time. They were also asked to complete a subjective assessment questionnaire. Results : The new ex vivo biological model had both content and construct validity. On comparison with the non-biological model, there was no statistically significant difference between the two models for time to puncture, total fluoroscopy exposure, and also the number of attempts taken for a successful puncture. The participants felt that the new biological model was better than the non-biological model in terms of overall assessment, tissue feel, and confidence in training. But the non-biological model scored better than the new biological model for ease of puncture and model preparation. Conclusion : The present model is inexpensive and easy to construct, and has both content and construct validity. It is a feasible model for fluoroscopy-guided PRA. Abbreviations: 3D: three-dimensional; PCNL: percutaneous nephrolithotomy; PRA: percutaneous renal access; VR: virtual reality